Ambulatory patients with spina bifida are 50% more likely to be fecally continent than non-ambulatory patients, particularly after a MACE procedure. Issue 1 (February 2017) - Large, T.; Szymanski, K.M.; Whittam, B.; Misseri, R.; Chan, K.H.; Kaefer, M.; Rink, R.C.; Cain, M.P.
Summary: Introduction: While fecal incontinence (FI) affects many patients with spina bifida (SB), it is unclear if it is associated with ambulatory status. Objective: To determine if ambulatory status is associated with FI, and a potential confounding variable, in patients with and without a Malone antegrade continence enema (MACE). Study design: This study retrospectively reviewed of patients aged ≥8 years with SB who were enrolled in an international quality of life study at outpatient visits (January 2013 to September 2015). Patients reported FI over the last 4 weeks (strict criteria: any FI/accidents vs no FI). Patients unable to self-report FI due to developmental delay were excluded. Those who were ambulating outdoors with/without braces/crutches were considered community ambulators. Non-parametric tests and logistic regression were used for analysis. Results: A total of 115 patients with a MACE and 57 without a MACE were similar in gender ( P = 0.99), ventriculoperitoneal status ( P = 0.15) and age (16.0 vs 15.4 years, P = 0.11). Median ages at MACE procedure and follow-up were 7.0 and 8.2 years, respectively, and all used the MACE ≥3x/week. They were less likely to be ambulators (54.8 vs 71.9%, P = 0.03). In patients with a MACE, 64 (55.7%) had total fecal continence, compared with 29 (50.9%) without a MACE ( P = 0.62). In the MACE group, ambulators were more likely to be continent compared with non-ambulatory patients (65.1 vs 44.2%, P = 0.04) (Table). Although not statistically significant, a similar difference was observed in the non-MACE group (56.1 vs 37.5%, P = 0.25). In the MACE group, continent and incontinent patients, regardless of ambulatory status, had similar rates of MACE use, additive use and time for MACE completion ( P ≥ 0.43). MACE ambulators were more likely to be continent than MACE non-ambulators on multivariate analysis (OR 3.26, P = 0.01). Discussion: This study reported higher than typical FI rates since: (1) it used a stringent definition of total fecal continence; (2) patients without FI were perhaps less likely to participate; and (3) it relied on patient-reported rather than clinician-reported outcomes. This cross-sectional study should not be interpreted as "MACE procedure is ineffective;" this would require a longitudinal study. The present findings may not apply to young children or those with significant developmental delay (patients excluded from the study). Conclusions: Ambulatory patients with SB are 50% more likely to have total fecal continence on long-term follow-up, particularly after a MACE procedure. Ambulatory status is a significant confounder of FI and should be considered in future analyses. Summary table Predictors of fecal continence after MACE procedure. Patient characteristic No MACE ( n = 57) MACE ( n = 115) Non-ambulatory 6/16 (37.5%) 23/52 (44.2%) Ambulatory 23/41 (56.1%) 41/63 (65.1%) P -value 0.25 0.04 MACE, Malone antegrade continence enema.